Domestic labor, foreign capital and national welfare - Udo Broll; Sabine Hansen; Sugata Marjit (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2004)
The competitive allocation of labor across different sectors of an economy may not be socially optimal when one sector uses foreign capital. We argue that a suitably designed government intervention is required to restrict the sectors to their optimal size and maximize national welfare. Such a policy internalizes the possibility of repatriation and reinvestment. We demonstrate the optimality of a minimum wage regulation.
Keywords: F16; F21; 330; Foreign capital; factor mobility; national welfare; targeting; Arbeitsmarktpolitik; Direktinvestition; Internationale Faktormobilität; Internationale Arbeitsmobilität; Mindestlohn; Mehr-Sektoren-Modell; Wohlfahrtseffekt; Theorie